Amidinate-stabilized silicon and germanium complexes. - Zhang, Shuhua (2014)
Synthesis and characterization of novel amidinate-stabilized silicon and germanium complexes were described. They include monomeric silylsilylenes, potassium siladithiocarboxylate, singlet delocalized 2,4-diimino-1,3-disilacyclobutanediyl, silylenylsilaimine, Si4 ring which consists of an aromatic silicon-containing four-membered ring and its reactivity with elemental sulfur and bisgermylene oxide and sulphide.